SELF DISCLOSURE IN COUNSELING PROCESS (A CASE STUDY OF FEMALE STREET CHILDREN CLIENTS WHO BECOME VICTIMS OF SEXUAL HARRASMENT) - Mulawarman Mulawarman (Universitas Negeri Malang, 2014)
Abstract: The purpose of this research was to describe self disclosure in counseling process of female street children clients who become victims of sexual harassment. This study used a qualitative descriptive case study design. The main data sources are the female street children at the city of Semarang. The data collection techniques data were: in-depth interviews, focus group discussion, and use of documents. Data analysis techniques used was an interactive analytical model. Examination of the validity of the data was done by using triangulation. Results showed Female street children are able to reveal the relevant information from their sexual harassment experience at length but with slightly lowered tone of voice. Results showed female street children became easier to disclose the sexual harrasment experience when counselors also disclose his personal experiences to them. She prefers to say the bad experience to other women than with men. When they revealed that experience they tend to tell it calmly but sometimes their emotion was reflected in their gesture. Keywords: self disclosure, counseling process, female street children clients, victims of sexual harassment.